Determinasi Net Profit Margin, Debt to Assets Ratio, dan Operating Profit Margin terhadap Return On Assets pada PT FKS Food Sejahtera Tbk Periode 2015-2024 - Khaerunnisa, Syifa; Herlinawati, Erna; Syarif, Devyanthi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
During the research period, this study aims to examine the effect of Net Profit Margin, Debt to Assets Ratio, and Operating Profit Margin on Return on Assets. This research employs a quantitative approach using descriptive and verificative methodologies to analyze the relationship between profitability ratios, leverage, and company financial performance. The data used in this study consist of secondary data obtained from companies’ annual reports and publicly available financial statements, which were collected using appropriate sampling techniques based on predetermined research criteria. Data analysis was conducted using IBM SPSS Statistics version 25. Hypothesis testing was performed through partial tests to evaluate the individual effect of each independent variable on ROA, as well as simultaneous tests to assess their collective influence. The results of the partial analysis indicate that Net Profit Margin and Operating Profit Margin have a significant effect on Return on Assets, suggesting that higher levels of profitability contribute positively to the efficiency of asset utilization. In contrast, the Debt to Assets Ratio does not show a significant effect on ROA, indicating that the level of leverage does not directly determine asset performance. However, the simultaneous test results reveal that NPM, DAR, and OPM jointly have a significant impact on ROA. These findings imply that while debt proportion alone may not be a dominant factor, profitability indicators play a crucial role in enhancing company performance. Therefore, companies are encouraged to focus on strategies that improve net profit and operational efficiency to optimize asset performance and achieve sustainable growth